(untitled) (HIMALAYA, 2019)
Malaria is a disease that has blighted humankind since early times. The first antimalarial treatment available to Europeans was the dried bark of the cinchona tree from Peru. The main problem in its use was adulteration by other material. The ‘active principle’ was first extracted in 1820 and named quinine. It was found to be a more powerful and reliable drug than cinchona bark. Once its chemical structure had been determined, it was possible to synthesize substances chemically related to quinine that were equally powerful but could be manufactured industrially. Mepacrine (atabrine) was amongst the most successful, but had adverse side effects. To avoid these side effects, further chemical modification gave chloroquine, a highly successful drug. This sequence is a common way of converting an herbal remedy into a modern-style chemical drug. It parallels, to some extent, the process of potentiation common in traditional herbal medicine. By the 1970s, drug resistance had developed with chloroquine. To find and develop a new antimalarial drug that worked on an entirely different pharmacological principle, Chinese scientists turned to their herbal compendia (ben cao) and found that Artemisia annua (qing hao) was frequently mentioned as a treatment for intermittent fever. Whether, in view of the distinctive doctrines of Chinese medicine, it should be possible to extract an active principle as described above is discussed. After a very careful reading of the procedure given for the use of qing hao, an active substance, artemisinin, was extracted. Artemisinin has a truly remarkable chemical structure, and chemical modification produced artesunate, the drug of choice. To prevent the development of resistance, artesunate is used in combination with other antimalarial drugs. Modern pharmacology has largely ignored that other substances in artemisia and the cinchona bark may contribute to their therapeutic effect. This matter is also discussed.